(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
With the signature of the controversial nuclear agreement with Iran, the Middle East could reshape once again its regional equilibrium and deterrence logics. Nevertheless, this historical moment brings one more time an opportunity to review the deterrence theory, its weakness and strengthens but above all, represents a chance to look into the future alternatives to weapons of mass destruction as arms controls initiatives or regional disarmament processes. Without being an easy process with just a single and correct answer, this paper examines the current evolution of the theory as well as in the Middle East case analyzing its future plausible options